Evaluation of noise values and homogenity of CT scan image results on head phantom after daily calibration - Samaliwu, Evelin Trivena; Illya, Gregoria (Universitas Riau, 2025)
Evaluation of CT scan image quality is a crucial aspect in ensuring accurate medical diagnosis. This research aims to evaluate noise values and image homogeneity of CT scans on a head phantom after daily calibration. Evaluation of these two parameters is critical because high noise can interfere with image contrast and lead to clinical misinterpretation, while low homogeneity may indicate artifacts or system inconsistencies that potentially reduce diagnostic reliability. Measurements were performed using Region of Interest (ROI) at five points (one in the center and four at the edges at 12, 3, 6, and 9 o'clock positions) across six image slices, for both head and body modes. The CT scan system used was Siemens SOMATOM go.Top, with primary scanning parameters for each mode: 120 kV voltage, 265 mA current (head) and 220 mA (body), as well as Hr40f and Br40f kernels. Research results show that the CT number homogeneity values in head mode ranged from -1.96 to 0.81 HU, and in body mode from -1.78 to 1.28 HU; all were within the tolerance limit of 0 ± 4 HU. Noise values for head mode ranged from 3.49 – 3.67 HU and body mode from 4.98 – 5.37 HU, also within standard tolerance limits. These findings indicate that the CT scan system functions properly and meets diagnostic imaging quality standards. Additionally, these results support the importance of implementing periodic quality control as part of improving radiological service quality and strengthening patient safety standards in medical facilities.